Multinational Corporations vs. Domestic Corporations: Financial Performance and Characteristics - Michel, Allen; Shaked, Israel (Journal of International Business Studies, 1986)
The analysis in this paper is composed of two segments. First, the financial performance of a sample of multinational corporations (MNCs) is compared with that derived for a control group of domestic corporations (DMCs) using market-based performance measures. Then, the paper presents a comparison of selected financial characteristics of the firms in the two groups. The results suggest the DMCs appear to have a significantly superior risk-adjusted market-based performance, are significantly less capitalized, and have higher total risk as well as higher systematic risk. The fact that MNCs are substantially larger than DMCs is not found to be a significant factor in explaining the observed difference between the two groups' performance.